Efficacy and safety of itacitinib versus placebo in combination with corticosteroids for initial treatment of acute graft-versus-host disease (GRAVITAS-301): a randomised, multicentre, double-blind, phase 3 trial. Issue 1 (January 2022) - Zeiser, Robert; Socié, Gérard; Schroeder, Mark A; Abhyankar, Sunil; Vaz, Carlos Pinho; Kwon, Mi; Clausen, Johannes; Volodin, Leonid; Giebel, Sebastian; Chacon, Manuel Jurado; Meyers, Gabrielle; Ghosh, Monalisa; et al.
Summary: Background: Acute graft-versus-host disease (GVHD) is a common and life-threatening complication of allogeneic haematopoietic stem cell transplantation (HSCT); there is an urgent unmet need for effective therapies. We aimed to evaluate the Janus kinase 1 inhibitor itacitinib versus placebo, both in combination with corticosteroids, for initial treatment of acute GVHD. Methods: GRAVITAS-301 was an international, double-blind, adaptive (group sequential design) phase 3 study conducted at 129 hospitals and community practices in 19 countries. Eligible patients were aged 18 years or older, had previously received allogeneic HSCT for a haematological malignancy, developed grades II–IV acute GVHD, and received up to 2 days of systemic corticosteroids. Patients were stratified by clinical standard-risk or high-risk acute GVHD and randomly assigned (1:1), via a centralised interactive voice response system, to receive either oral itacitinib (200 mg) or placebo once daily, both in addition to corticosteroids. The primary endpoint was overall response rate (ORR) at day 28 (defined as the proportion of patients with complete response, very good partial response, or partial response 28 days after the start of treatment). For sample size determination, an absolute improvement in ORR at day 28 over standard therapy of 16% was considered clinically meaningful. Efficacy analyses were performed in the intention-to-treat population; safety analyses included patients who received at least one dose of study drug. GRAVITAS-301 is registered with ClinicalTrials.gov (NCT03139604 ) and is complete. Findings: Between July 19, 2017, and Oct 3, 2019, 439 patients were randomly assigned to receive either itacitinib plus corticosteroids (n=219; itacitinib group) or placebo plus corticosteroids (n=220; placebo group). 173 (39%) patients were female and 390 (89%) were White. At baseline, 107 (24%) of 439 patients (itacitinib 51 [23%] of 219; placebo 56 [25%] of 220) had clinical high-risk acute GVHD. The ORR at day 28 was 74% (95% CI 67·6–79·7; 162 of 219; complete response 53% [116 of 219]) for itacitinib and 66% (59·7–72·6; 146 of 220; complete response, 40% [89 of 220]) for placebo (odds ratio for ORR 1·45, 95% CI 0·96–2·20; two-sided p=0·078). Grade 3 or worse adverse events occurred in 185 (86%) of 215 itacitinib recipients and 178 (82%) of 216 placebo recipients, and most commonly included thrombocytopenia or platelet count decreased (78 [36%] vs 68 [31%]), neutropenia or neutrophil count decreased (49 [23%] vs 45 [21%]), anaemia (42 [20%] vs 26 [12%]), and hyperglycaemia (26 [12%] vs 28 [13%]). Treatment-related deaths occurred in three of 215 patients (1%) in the itacitinib group and four of 216 (2%) in the placebo group. Interpretation: The observed improvement in ORR at day 28 with the addition of itacitinib versus placebo to corticosteroids did not reach the prespecified significance level. Further studies might provide additional insight into the utility of selective JAK1 inhibition for the treatment of acute GVHD. Funding: Incyte.